Illegal cannabis cultivation in Europe: new developments - David Weinberger; Michel Gandilhon; Jalpa Shah; Nacer Lalam (EchoGéo)
Herbal cannabis is one of the most consumed illegal drugs in Europe, with increasing local production. Illicit cannabis cultivation is not new to Western Europe. It first emerged on the scene in the 1970s, in the wake of the counter-culture following the 1968 Protests. Since then, it has gradually become more professional due to the increased diversification of involved actors, such as Organized Crime Groups (OCG), and the growing role of players linked to mafia organizations in both Italy and Albany. In Spain and France, where Moroccan resin has long dominated supply and demand, the cannabis market has seen a rise in herbal cannabis production. This, in turn, challenges the role of OCGs invested in resin importation. Yet, European marihuana production cannot be defined as a strictly criminal business. Small growers remain significant actors in production. This trend in production must be examined against evolving attitudes towards marihuana at the global level, linked especially to new legislation in the United States and in Canada.